2021
DOI: 10.1017/jfm.2021.66
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic attachment-line instabilities with large sweep Mach numbers

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 63 publications
(96 reference statements)
5
11
4
Order By: Relevance
“…Moreover, we found that the N-S mean flow solutions, which were used by Xi et al. (2021) in their stability analyses, do not agree with our N-S solutions and the compressible Hiemenz solution, which casts doubt on the correctness of the results reported.…”
Section: Introductioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Moreover, we found that the N-S mean flow solutions, which were used by Xi et al. (2021) in their stability analyses, do not agree with our N-S solutions and the compressible Hiemenz solution, which casts doubt on the correctness of the results reported.…”
Section: Introductioncontrasting
confidence: 80%
“…In addition to reconsidering the cases reported by Xi et al. (2021) and correcting their results, this paper suggests a theoretical model, which captures the attachment-line modes and allows us to determine regions of their dominance in the space. This model helps to perform quick parametric studies of the compressible attachment-line instability, shed light on the mechanisms of instability and extrapolate the knowledge gained on the supersonic boundary layer stability to the attachment-line flow.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations